THE EFFECT OF RETURN ON ASSETS, RETURN ON EQUITY, AND NET PROFIT MARGIN ON STOCK PRICES IN FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2019-2021 PERIOD - Andi Alfiyah Ilyas; M. Ikhwan Maulana Haeruddin; Anwar; Romansyah Sahabuddin; Muh. Ichwan Musa (Transpublika Publisher, 2023)
Fundamental analysis is a widely used approach for predicting stock price movements. This study aims to investigate the impact of return on assets (ROA), return on equity (ROE), and net profit margin (NPM) on the stock prices of food and beverage companies listed on the Indonesia Stock Exchange during the period of 2019-2021. The research is based on secondary data from 84 samples. The data analysis employs multiple linear regression using the SPSS version 22 application. The findings reveal that return on assets and net profit margin do not exhibit significant effects and have a negative influence on stock prices. Conversely, return on equity demonstrates a significant and positive correlation with stock prices. Overall, the study indicates that ROA, ROE, and NPM significantly impact stock prices. As a recommendation, investors should closely analyze ROA, ROE, NPM, and stock price movements to enhance their profitability.